2013
DOI: 10.1371/journal.pone.0057634
|View full text |Cite
|
Sign up to set email alerts
|

A Serratia marcescens PigP Homolog Controls Prodigiosin Biosynthesis, Swarming Motility and Hemolysis and Is Regulated by cAMP-CRP and HexS

Abstract: Swarming motility and hemolysis are virulence-associated determinants for a wide array of pathogenic bacteria. The broad host-range opportunistic pathogen Serratia marcescens produces serratamolide, a small cyclic amino-lipid, that promotes swarming motility and hemolysis. Serratamolide is negatively regulated by the transcription factors HexS and CRP. Positive regulators of serratamolide production are unknown. Similar to serratamolide, the antibiotic pigment, prodigiosin, is regulated by temperature, growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 71 publications
(105 reference statements)
2
48
0
Order By: Relevance
“…Serratamolide also is required for swarming motility in many strains of S. marcescens (25,42). We observed that eepR and eepS mutants were defective in swarming in the wild-type (CMS376) and K904 strain backgrounds (Fig.…”
Section: Identification Of Eepr and Eepsmentioning
confidence: 67%
See 3 more Smart Citations
“…Serratamolide also is required for swarming motility in many strains of S. marcescens (25,42). We observed that eepR and eepS mutants were defective in swarming in the wild-type (CMS376) and K904 strain backgrounds (Fig.…”
Section: Identification Of Eepr and Eepsmentioning
confidence: 67%
“…An MBP fusion to EepR (MBP-EepR) and MBP alone were generated for affinity purification of EepR using pMal-C2 (New England BioLabs) as previously described (25). His 8 -CRP purification was described previously (18).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA was extracted from cultures grown in LB broth to an OD 600 of 3.0 using a Qiagen RNA Easy kit, and cDNA preparations were performed as previously described (41). Two rounds of DNase treatment were performed to remove chromosomal DNA.…”
Section: Reverse Transcription-pcr (Rt-pcr)mentioning
confidence: 99%